Análise experimental de pisos mistos de madeira e concreto de pós-reativos (CPR) - BRITTO, Raimundo Angelo de Lima (Universidade Federal do Pará, 2018)
Mixed timber and concrete structures have long been part of the constructive context around the world, and are mainly used for the recovery of old wooden floors in single or multi-family dwellings, mainly in European and North American countries, are used Also in structures of bridges and walkways in the open air since the concrete plate protects the wood from the elements, solar radiation among others. Several factors contribute to the use of this type of structure in homes, among them the following: the cost much cheaper than the conventional construction in reinforced concrete, the architectural lightness of the arrangement, with the apparent varnished wood and painted slabs, Providing a very good finish, thermal and acoustic insulation if we take as a reference the only wooden floors. This work highlights the use of wood from reforestation in Brazil, being chosen for its beauty and resistance to Tectona Grandis (TECA), and for the slab that compose the table we chose a concrete of post reactive, where some aggregates are by-products of the industries of Paper and glass. The geometry drawn for slab was outlined in search of having the best structural arrangement, combined with the good architectural effect. The expressions for calculating the mixed wood-concrete floor are based on the equilibrium equations and the precepts of EUROCODE 5, the parameters for verification and safety follow the precepts of NBR 7190/97, NBR 6118/14 of EUROCODE 5 itself. The results show that there are significant differences between the analytical and finite element methods (SAP 2000), the results between these models had significant differences, as far as the experimental model, the measurements performed showed a much higher stiffness than those presented In the two models mentioned above. We conclude that the elasticity moduli of the materials and the sliding modulus must be tested in order to be close to experimental results. The results obtained in the experimental model showed us excellent rigidity, the safety factors regarding the EL and final use were met the final cost of assembly even with the use of the post-reactive concrete was lower than the cost of a conventional structure , Thus we can denote that the concrete-wood structures present great conditions of use in constructions and reforms, being of the utmost importance the incentive and the continuity of this constructive technique.